Multicomponent bionanocomposites based on clay nanoarchitectures for electrochemical devices - Lo Dico, Giulia; Wicklein, Bernd; Lisuzzo, Lorenzo; Lazzara, Giuseppe; Aranda, Pilar; Ruiz-Hitzky, Eduardo (Beilstein Journal of Nanotechnology, 2019)
Based on the unique ability of defibrillated sepiolite (SEP) to form stable and homogeneous colloidal dispersions of diverse types of nanoparticles in aqueous media under ultrasonication, multicomponent conductive nanoarchitectured materials integrating halloysite nanotubes (HNTs), graphene nanoplatelets (GNPs) and chitosan (CHI) have been developed. The resulting nanohybrid suspensions could be easily formed into films or foams, where each individual component plays a critical role in the biocomposite: HNTs act as nanocontainers for bioactive species, GNPs provide electrical conductivity (enhanced by doping with MWCNTs) and, the CHI polymer matrix introduces mechanical and membrane properties that are of key significance for the development of electrochemical devices. The resulting characteristics allow for a possible application of these active elements as integrated multicomponent materials for advanced electrochemical devices such as biosensors and enzymatic biofuel cells. This strategy can be regarded as an “a la carte” menu, where the selection of the nanocomponents exhibiting different properties will determine a functional set of predetermined utility with SEP maintaining stable colloidal dispersions of different nanoparticles and polymers in water.
Keywords: bionanocomposites; carbon nanostructures; electrochemical devices; halloysite nanotubes; sepiolite

(untitled) - Aono, M.; Bando, Y.; Ariga, K. (Adv. Mater. (Weinheim, Ger.), 2012)

Manipulation of Nanoscale Materials: An Introduction to Nanoarchitectonics - Ariga, K. (Royal Society of Chemistry, 2012)

(untitled) - Komiyama, M.; Yoshimoto, K.; Sisido, M.; Ariga, K. (Bull. Chem. Soc. Jpn., 2017)

(untitled) - Khan, A. H.; Ghosh, S.; Pradhan, B.; Dalui, A.; Shrestha, L. K.; Acharya, S.; Ariga, K. (Bull. Chem. Soc. Jpn., 2017)

(untitled) - Ariga, K.; Mori, T.; Shrestha, L. K. (Chem. Rec., 2018)

(untitled) - Kryuchkova, M.; Fakhrullin, R. (Environ. Sci. Technol. Lett., 2018)

Manipulation of Nanoscale Materials: An Introduction to Nanoarchitectonics - Ruiz-Hitzky, E.; Aranda, P.; Belver, C. (Nanoarchitectures Based on Clay Materials, 2012)

(untitled) - Aranda, P.; Ruiz-Hitzky, E. (Chem. Rec., 2018)

(untitled) - Vinokurov, V. A.; Stavitskaya, A. V.; Glotov, A. P.; Novikov, A. A.; Zolotukhina, A. V.; Kotelev, M. S.; Gushchin, P. A.; Ivanov, E. V.; Darrat, Y.; Lvov, Y. M. (Chem. Rec., 2018)

(untitled) - Glotov, A.; Levshakov, N.; Stavitskaya, A.; Artemova, M.; Gushchin, P.; Ivanov, E.; Vinokurov, V.; Lvov, Y. (Chem. Commun., 2019)

(untitled) - Li, L.; Ma, W.; Higaki, Y.; Kamitani, K.; Takahara, A. (Langmuir, 2018)

(untitled) - Fu, L.; Yang, H.; Tang, A.; Hu, Y. (Nano Res., 2017)

(untitled) - Lazzara, G.; Cavallaro, G.; Panchal, A.; Fakhrullin, R.; Stavitskaya, A.; Vinokurov, V.; Lvov, Y. (Curr. Opin. Colloid Interface Sci., 2018)

(untitled) - Lvov, Y.; Wang, W.; Zhang, L.; Fakhrullin, R. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Cavallaro, G.; Lazzara, G.; Milioto, S.; Parisi, F.; Evtugyn, V.; Rozhina, E.; Fakhrullin, R. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Lo Dico, G.; Semilia, F.; Milioto, S.; Parisi, F.; Cavallaro, G.; Inguì, G.; Makaremi, M.; Pasbakhsh, P.; Lazzara, G. (Appl. Sci., 2018)

(untitled) - Tully, J.; Yendluri, R.; Lvov, Y. (Biomacromolecules, 2016)

(untitled) - Lvov, Y. M.; Shchukin, D. G.; Möhwald, H.; Price, R. R. (ACS Nano, 2008)

(untitled) - Shchukin, D. G.; Sukhorukov, G. B.; Price, R. R.; Lvov, Y. M. (Small, 2005)

(untitled) - Kumar-Krishnan, S.; Hernandez-Rangel, A.; Pal, U.; Ceballos-Sanchez, O.; Flores-Ruiz, F. J.; Prokhorov, E.; Arias de Fuentes, O.; Esparza, R.; Meyyappan, M. (J. Mater. Chem. B, 2016)

(untitled) - Goda, E. S.; Gab-Allah, M. A.; Singu, B. S.; Yoon, K. R. (Microchem. J., 2019)

(untitled) - Sun, X.; Zhang, Y.; Shen, H.; Jia, N. (Electrochim. Acta, 2010)

(untitled) - Cavallaro, G.; Lazzara, G.; Milioto, S. (J. Phys. Chem. C, 2012)

Natural mineral nanotubes, properties and applications - Pasbakhsh, P.; Chrichman, G. J. (Apple Academic Press Inc., 2015)

(untitled) - Fernandes, F. M.; Ruiz-Hitzky, E. (Carbon, 2014)

(untitled) - Ruiz-Hitzky, E.; Sobral, M. M. C.; Gómez-Avilés, A.; Nunes, C.; Ruiz-García, C.; Ferreira, P.; Aranda, P. (Adv. Funct. Mater., 2016)

(untitled) - Ruiz-Hitzky, E. (J. Mater. Chem., 2001)

Functional Polymer Composites with Nanoclays - Ruiz-Hitzky, E.; Darder, M.; Alcântara, A. C. S.; Wicklein, B.; Aranda, P. (Functional nanocomposites based on fibrous clays, 2017)

(untitled) - González del Campo, M. M.; Darder, M.; Aranda, P.; Akkari, M.; Huttel, Y.; Mayoral, A.; Bettini, J.; Ruiz-Hitzky, E. (Adv. Funct. Mater., 2018)

(untitled) - Bertolino, V.; Cavallaro, G.; Lazzara, G.; Merli, M.; Milioto, S.; Parisi, F.; Sciascia, L. (Ind. Eng. Chem. Res., 2016)

(untitled) - Makaremi, M.; Pasbakhsh, P.; Cavallaro, G.; Lazzara, G.; Aw, Y. K.; Lee, S. M.; Milioto, S. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Wang, Y.; Qi, W.; Huang, R.; Su, R.; He, Z. (Adv. Mater. Interfaces, 2016)

(untitled) - Deuber, F.; Mousavi, S.; Federer, L.; Adlhart, C. (Adv. Mater. Interfaces, 2017)

(untitled) - Sun, J.; Yendluri, R.; Liu, K.; Guo, Y.; Lvov, Y.; Yan, X. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Yang, Y.; Yang, X.; Tan, Y.; Yuan, Q. (Nano Res., 2017)

(untitled) - Bhadra, J.; Popelka, A.; Abdulkareem, A.; Ahmad, Z.; Touati, F.; Al-Thani, N. (RSC Adv., 2019)

(untitled) - Ghimire, A.; Pattammattel, A.; Maher, C. E.; Kasi, R. M.; Kumar, C. V. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Kang, Z.; Jiao, K.; Yu, C.; Dong, J.; Peng, R.; Hu, Z.; Jiao, S. (RSC Adv., 2017)

(untitled) - Tiwari, J. N.; Vij, V.; Kemp, K. C.; Kim, K. S. (ACS Nano, 2016)

(untitled) - Voiry, D.; Chhowalla, M.; Gogotsi, Y.; Kotov, N. A.; Li, Y.; Penner, R. M.; Schaak, R. E.; Weiss, P. S. (ACS Nano, 2018)

(untitled) - El-Gendy, D. M.; Abdel Ghany, N. A.; Allam, N. K. (RSC Adv., 2019)

(untitled) - Wicklein, B.; Diem, A. M.; Knöller, A.; Cavalcante, M. S.; Bergström, L.; Bill, J.; Burghard, Z. (Adv. Funct. Mater., 2018)

(untitled) - Wicklein, B.; Kocjan, A.; Salazar-Alvarez, G.; Carosio, F.; Camino, G.; Antonietti, M.; Bergström, L. (Nat. Nanotechnol., 2015)

(untitled) - Yan, J.; Wu, T.; Ding, Z.; Li, X. (Carbohydr. Polym., 2016)

(untitled) - Wu, Y.; Wang, Z.; Liu, X.; Shen, X.; Zheng, Q.; Xue, Q.; Kim, J.-K. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Żbik, M. S.; Raftery, N. A.; Smart, R. S. C.; Frost, R. L. (Appl. Clay Sci., 2010)

(untitled) - Svagan, A. J.; Berglund, L. A.; Jensen, P. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Darder, M.; López-Blanco, M.; Aranda, P.; Aznar, A. J.; Bravo, J.; Ruiz-Hitzky, E. (Chem. Mater., 2006)

Cellular Solids: Structure and Properties - Gibson, L. J.; Ashby, M. F. (Cambridge University Press, 1999)

(untitled) - Wicklein, B.; Aranda, P.; Ruiz-Hitzky, E.; Darder, M. (J. Mater. Chem. B, 2013)

(untitled) - Padilla-Ortega, E.; Darder, M.; Aranda, P.; Figueredo Gouveia, R.; Leyva-Ramos, R.; Ruiz-Hitzky, E. (Appl. Clay Sci., 2016)

(untitled) - Xu, Y.; Sheng, K.; Li, C.; Shi, G. (ACS Nano, 2010)

(untitled) - Obrey, K. A. D.; Wilson, K. V.; Loy, D. A. (J. Non-Cryst. Solids, 2011)

(untitled) - Shaari, N.; Kamarudin, S. K. (J. Power Sources, 2015)

(untitled) - Bai, H.; Zhang, H.; He, Y.; Liu, J.; Zhang, B.; Wang, J. (J. Membr. Sci., 2014)

(untitled) - Vasileiou, A. A.; Kontopoulou, M.; Gui, H.; Docoslis, A. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Vasileiou, A. A.; Docoslis, A.; Kontopoulou, M.; Xiang, P.; Ye, Z. (Polymer, 2013)

(untitled) - Wicklein, B.; Darder, M.; Aranda, P.; Ruiz-Hitzky, E. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Wicklein, B.; Martín del Burgo, M. Á.; Yuste, M.; Darder, M.; Llavata, C. E.; Aranda, P.; Ortin, J.; del Real, G.; Ruiz-Hitzky, E. (Eur. J. Inorg. Chem., 2012)

(untitled) - Muguruma, H.; Hoshino, T.; Nowaki, K. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Darder, M.; Takada, K.; Pariente, F.; Lorenzo, E.; Abruña, H. D. (Anal. Chem. (Washington, DC, U. S.), 1999)

(untitled) - Yokoyama, K.; Kayanuma, Y. (Anal. Chem. (Washington, DC, U. S.), 1998)

(untitled) - Darder, M.; Aranda, P.; Hernández-Vélez, M.; Manova, E.; Ruiz-Hitzky, E. (Thin Solid Films, 2006)

(untitled) - Choi, H. N.; Kim, M. A.; Lee, W.-Y. (Anal. Chim. Acta, 2005)

(untitled) - Wan, D.; Yuan, S.; Li, G. L.; Neoh, K. G.; Kang, E. T. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Zhu, N.; Han, S.; Gan, S.; Ulstrup, J.; Chi, Q. (Adv. Funct. Mater., 2013)

(untitled) - Papa, H.; Gaillard, M.; Gonzalez, L.; Chatterjee, J. (Biosensors, 2014)

(untitled) - Marand, Z. R.; Shahtahmassebi, N.; Housaindokht, M. R.; Rounaghi, G. H.; Razavipanah, I. (Electroanalysis, 2014)

(untitled) - Ji, J.; Joh, H.-I.; Chung, Y.; Kwon, Y. (Nanoscale, 2017)

(untitled) - Logan, B. E.; Hamelers, B.; Rozendal, R.; Schröder, U.; Keller, J.; Freguia, S.; Aelterman, P.; Verstraete, W.; Rabaey, K. (Environ. Sci. Technol., 2006)

(untitled) - Falk, M.; Blum, Z.; Shleev, S. (Electrochim. Acta, 2012)

(untitled) - Campbell, A. S.; Jeong, Y. J.; Geier, S. M.; Koepsel, R. R.; Russell, A. J.; Islam, M. F. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Liu, Y.; Zhang, J.; Cheng, Y.; Jiang, S. P. (ACS Omega, 2018)

(untitled) - Cinquin, P.; Gondran, C.; Giroud, F.; Mazabrard, S.; Pellissier, A.; Boucher, F.; Alcaraz, J.-P.; Gorgy, K.; Lenouvel, F.; Mathé, S.; Porcu, P.; Cosnier, S. (PLoS One, 2010)

(untitled) - Zebda, A.; Cosnier, S.; Alcaraz, J.-P.; Holzinger, M.; Le Goff, A.; Gondran, C.; Boucher, F.; Giroud, F.; Gorgy, K.; Lamraoui, H.; Cinquin, P. (Sci. Rep., 2013)

(untitled) - Trifonov, A.; Herkendell, K.; Tel-Vered, R.; Yehezkeli, O.; Woerner, M.; Willner, I. (ACS Nano, 2013)

(untitled) - Min, K.; Ryu, J. H.; Yoo, Y. J. (Biotechnol. Bioprocess Eng., 2010)

(untitled) - Falk, M.; Andoralov, V.; Blum, Z.; Sotres, J.; Suyatin, D. B.; Ruzgas, T.; Arnebrant, T.; Shleev, S. (Biosens. Bioelectron., 2012)

(untitled) - Garcia-Perez, T.; Hong, S.-G.; Kim, J.; Ha, S. (Enzyme Microb. Technol., 2016)

(untitled) - Reid, R. C.; Jones, S. R.; Hickey, D. P.; Minteer, S. D.; Gale, B. K. (Electrochim. Acta, 2016)